ATTENTION TO PROBLEMATIC SOCIAL GROUP REPRESENTATION IN GUIDANCE FOR USING MASS MEDIA IN ENGLISH EDUCATION - Brown, Charles Allen (LLT Journal: A Journal on Language and Language Teaching, 2024)
While media studies amply document problematic social group representation in mass media materials, how English language educators are equipped to address these issues when they engage in the common practice of appropriating such artifacts for teaching is unclear. This research responds by collecting 319 prominent Internet sources providing guidance on using mass media materials for language learning and subjecting them to a content analysis. This analysis draws upon ten forms of problematic social group portrayal in the mass media as a conceptual lens. Analysis results indicate little attention to ableism, ageism, Christonormativity, classism, colorism, gender bias, heternormativity, lookism/sizeism, racism, and urbanormativity with articles universally acclaiming the integration of mass media materials into language teaching, primarily on the grounds of “authenticity.” Defined as materials authored by and for native speakers, this is an authenticity insensitive to authentic social group representation. This research is significant because of teacher reliance on the Internet as a source of materials, because of the global reach of English language teaching, the power of mass media, especially for youth socialization, and because there is a lack of previous research concerning how language teachers are trained to consider problematic social group representation in mass media artifacts.